Open source jihad: problematizing the academic discourse on Islamic terrorism in contemporary Europe - Nilsson, Per-Erik (Cambridge elements, 2018)
In Open Source Jihad, Per-Erik Nilsson provides a unique overview of the academic research and political legislation concerning 'Islamic terrorism' in Europe. He scrutinises in detail how the concepts 'terrorism', 'radicalisation', and 'counter-terrorism' have developed as academic objects of study and political objects of governance. In the Element, Nilsson brings to the fore systemic problems of the field of terrorism studies as well as the various anti-terrorist apparatuses developed by EU member states. Open Source Jihad should be required reading for anyone interested in current European political and social events